The The Length Of Stay In Patients Undergoing Diagnostic MRI And CT-Scan With Intravenous Anesthesia At Outpatient Clinic Dr. Soetomo General Hospital: An Overview - Virda Maharani; Arie Utariani; Lucky Andriyanto; Bambang Harjono (Jurnal Ilmiah Kesehatan, 2021)
Background: Magnetic Resonance Imaging (MRI) and Computerized Tomography (CT) Scans might be challenging for children or patients with anxiety or claustrophobia. The use of general anesthesia aims to increase the success rate, but inadequate management can result in longer length of stay. Purpose: To analyze patients' length of stay on MRI and CT-scan with intravenous anesthesia. Methods: A descriptive observational study. The datas were collected retrospectively from the medical records in General Diagnostic Center. Total of 721 patients who underwent MRI or CT Scan procedures with intravenous anesthesia during 2017-2018. The data obtained were patients' age, sex, the type of procedure, physical status, comorbid, type of anesthesia drug, diagnostic procedure duration, length of observation in the Post Anesthesia Care Unit (PACU), and overall length of stay. Results: All MRI procedures used midazolam-propofol combination, and only one CT scan procedure used this combination, while the other used only propofol. Patients undergoing MRI had length of stay with a mean duration of 6,6,3±1,26 hours, compared to CT scans with 5,20 ±1,38 hours, due to the more prolonged procedure and observation duration in the PACU. Conclusion: Patients undergoing MRI had a longer length of stay than the ones doing CT scans.